Actin binding to galectin-13/placental protein-13 occurs independently of the galectin canonical ligand-binding site. (31st May 2021) - Li, Xumin; Yao, Yuan; Liu, Tianhao; Gu, Keqi; Han, Qiuyu; Zhang, Wenlu; Ayala, Gabriela Jaramillo; Liu, Yuhan; Na, Heya; Yu, Jinyi; Zhang, Fan; Mayo, Kevin H; et al.
Abstract: The gene for galectin-13 (Gal-13, placental protein 13) is only present in primates, and its low expression level in maternal serum may promote preeclampsia. In the present study, we used pull-down experiments and biolayer interferometry to assess the interaction between Gal-13 and actin. These studies uncovered that human Gal-13 (hGal-13) and Saimiri boliviensis boliviensis (sGal-13) strongly bind to α- and β-/γ-actin, with Ca 2+ and adenosine triphosphate, significantly enhancing the interactions. This in turn suggests that h/sGal-13 may inhibit myosin-induced contraction when vascular smooth muscle cells undergo polarization. Here, we solved the crystal structure of sGal-13 bound to lactose and found that it exists as a monomer in contrast to hGal-13 which is a dimer. The distribution of sGal-13 in HeLa cells is similar to that of hGal-13, indicating that monomeric Gal-13 is the primary form in cells. Even though sGal-13 binds to actin, hGal-13 ligand-binding site mutants do not influence hGal-13/actin binding, whereas the monomeric mutant C136S/C138S binds to actin more strongly than the wild-type hGal-13. Overall, our study demonstrates that monomeric Gal-13 binds to actin, an interaction that is independent of the galectin canonical ligand-binding site.